Solve for y 18-5y=-3(y-2)

Math
18-5y=-3(y-2)
Simplify -3(y-2).
Tap for more steps…
Apply the distributive property.
18-5y=-3y-3⋅-2
Multiply -3 by -2.
18-5y=-3y+6
18-5y=-3y+6
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 3y to both sides of the equation.
18-5y+3y=6
Add -5y and 3y.
18-2y=6
18-2y=6
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 18 from both sides of the equation.
-2y=6-18
Subtract 18 from 6.
-2y=-12
-2y=-12
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=-12 by -2.
-2y-2=-12-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=-12-2
Divide y by 1.
y=-12-2
y=-12-2
Divide -12 by -2.
y=6
y=6
Solve for y 18-5y=-3(y-2)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top